2021
DOI: 10.14719/pst.1304
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variability and genetic diversity of Aman rice germplasm of Bangladesh cultivated in Mymensingh region

Abstract: Thirty-one Aman rice germplasm were evaluated to assess their morphological variability and genetic diversity considering ten quantitative and thirty one qualitative traits at the field experimental plot of Bangladesh Institute of Nuclear Agriculture, Mymensingh, following randomized complete block design. The germplasm showed significant differences for all the studied traits. The highest grain yield/plant was recorded in Sentu-16 whereas the lowest was found in Gaindha. The genotypic coefficient of variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
6
2
0
Order By: Relevance
“…The number of effective tillers per plant recorded with high values of phenotypic and genotypic coefficients of variation suggested that genetic control influenced these characteristics. Others also reported higher GCV and PCV for NFT (Ghosal et al, 2012;Emi et al, 2021) in agreement with these results. Hence, simple selection needs an application to further improve these traits.…”
Section: Discussionsupporting
confidence: 83%
“…The number of effective tillers per plant recorded with high values of phenotypic and genotypic coefficients of variation suggested that genetic control influenced these characteristics. Others also reported higher GCV and PCV for NFT (Ghosal et al, 2012;Emi et al, 2021) in agreement with these results. Hence, simple selection needs an application to further improve these traits.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, phenotypic selection might be beneficial in the improvement of traits under consideration. Days to maturity recorded the lowest PCV and GCV illustrating that there was meagre variation in these parameters and the results were in concordance with Aswin et al (2021) and Emi et al (2021). Moderate PCV and GCV were noticed for the plant height and length of the panicle similar to the findings of Bhargava et al (2021) and Prasannakumari et al (2020); grain L/B ratio in corroboration with the results of Roy et al (2021) and Aswin et al (2021) and for grain length reported by Priyanka and Gauraha (2020).…”
Section: Resultssupporting
confidence: 85%
“…Flag leaf length and hundred seed weight were found to have a positive significant correlation with panicle length. The number of tillers and the number of effective tillers per plant were intercorrelated to each other and were correlated positively and significantly with flag leaf breadth and the number of filled seed per panicle identical to the reports produced byEmi et al (2021) andKiruthikadevi et al (2020) for the number of filled grains per panicle. The number of filled grains per panicle reported a positive significant correlation with grain length, grain breadth and hundred seed weight similar to the findings byPrasannakumari et al (2020. A significant positive correlation was noticed between grain length and hundred seed weight similar to the documentation byManivelan et al (2022) andSeneega et al (2019).…”
supporting
confidence: 82%
“…In our present study, the analysis of genetic parameter revealed higher values of heritability for all the seven traits studied resulted from the narrower distance between genotypic and phenotypic variance which indicate the maximum genetic control and the minimum influence of environment on the expression of these traits. Similar to our results, higher GCV and PCV for these traits were also reported others (Ghosal et al, 2012;Emi et al, 2021). These findings suggest the successful phenotypic selection as an effective way for improvement of these traits (Bhadru et al, 2012).…”
Section: Genetic Variability Heritability and Genetic Advancesupporting
confidence: 92%